In Light Memory of the Ever-living (in Memory of Professor Jerzy Bartminskyi) (Linguostylistic Studies, 2022)
The article highlights the main areas of scientific self-realization of Professor Bartminskyi, whose scientific output includes 676 items, including 12 monographs and dictionaries, a significant part of which is devoted to studying stereotypes and folk symbols. The scholar considers them as the integral elements of the linguistic picture of the world of every ethnic group.In addition to ethnolinguistics, the main and permanent vector of the scientist's research interests, the research scope also included folkloristics, dialectology, stylistics, Slavic studies, cognitive linguistics, and axiology.The Dictionary of Stereotypes and Folk Symbols (Słownik stereotypów i symboliw ludowych) is one of the Jerzy Bartminskyi’s most famous works.The professor contributed greatly to the activities of the scientific and educational institutions of Poland, primarily owing to the creation of the Ethno-linguistic Center in Lublin, the organization and holding of numerous thematic seminars and conferences, the creation of an ethno-linguistic archive, supervising 300 master’s and 17 doctoral research studies, the initiation and long-term editorship of the popular in the scientific world annual Etnolingwistyka. ProblemyJęzyka i Kultury (vol.1–30, 1988–2018) and a collection of scientific papers Language and Culture (“Język a kultura”). An important aspect of his professional self-realization (especially estimable for Ukrainian philologists) was the opening of the Ukrainian Studies department at the Maria Curie-Skłodowska University of Lublin and at the Ivan Paul II Catholic University in Lublin, as well as constant cooperation with scientific linguistic societies in Ukraine, his direct participation in establishing the ethno-linguistic centers in Lviv and Zhytomyr, and active support of their activity.As the head of the Ethno-Linguistic Commission at the International Committee of Slavists, Professor Bartminskyi coordinated the work of ethno-linguistic centers throughout the Slavic world, determining priority areas of research and developing their methodology.Folkloristics was an important aspect of his scientific activities. A significant part of Jerzy Bartminskyi’s works is devoted to the issues of the oral poetic texts’ language and stylistics, mostly carols. These texts were not only the object of his study, but the professor himself collected, recorded, and compiled anthologies of Polish carols.The article also focuses on the personality qualities of the undoubtedly most outstanding linguist of the late 20th and early 21st centuries. The author argues that Jerzy Bartminskyi’s scientific works will serve as a reliable theoretical research framework for all future generations of linguists, primarily ethnolinguists.
Keywords: professional self-realization; ethnolinguistics; language; culture; stereotype